Nanohybrids based on multi-walled carbon nanotubes and MOF-199: Advantages on the electrochemical reduction of hydrogen peroxide and sensing applications - Gallay, Pablo (2025)
We report the advantages of a nanohybrid obtained through the integration of multi-walled carbon nanotubes (MWCNTs) and MOF-199 by sono-synthesis. The resulting nanohybrid presents important synergic effects on the catalytic reduction of hydrogen peroxide due to the facilitated regeneration of the catalytic center in the presence of the interconnected carbon nanomaterial. Glassy carbon electrodes (GCE) modified with this hybrid nanomaterial dispersed in Nafion allowed the sensitive quantification of hydrogen peroxide: linear range between 5.0 × 10-6 M and 7.5 × 10-5 M (R2 = 0.997), with a sensitivity of (128 ± 3) x 102 μA M-1, a detection limit of 2 μM, and a reproducibility of 8.0 % for the same nanohybrid and 5 different electrodes allowing the competitive electrochemical determination of hydrogen peroxide. The sensor was successfully used for the quantification of this important analyte in diverse commercial samples (milk, human serum, contact lens disinfecting solution, and mouthwash).